Q: What is -6x plus 3y equals -18 -10 plus 5y equals -30 using substitution?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

From first equation: y = 5 - 5xSubstitute for y in second equation: 3x + 10 - 10x = 3ie -7x = -7ie x = 1 and y = 0

By definition: 4x-10 = 5-x 4x+x = 5+10 5x = 15 x = 3 and y = 2

y = 4x-8 and y = 2x+10 4x-8 = 2x+10 4x-2x = 10+8 2x = 18 x = 9 Substitute the value of x into the original equations to find the value of y: Therefore: x = 9 and y = 28

This can be solved a number of ways. In thi case I prefer substitution. y-3=7 simplifies to y=10. Substitute 10 in for y so you get x+3(10)=6. Simplify this and you get x=-24

-4 plus 10 equals 6.

Related questions

From first equation: y = 5 - 5xSubstitute for y in second equation: 3x + 10 - 10x = 3ie -7x = -7ie x = 1 and y = 0

By definition: 4x-10 = 5-x 4x+x = 5+10 5x = 15 x = 3 and y = 2

y = 4x-8 and y = 2x+10 4x-8 = 2x+10 4x-2x = 10+8 2x = 18 x = 9 Substitute the value of x into the original equations to find the value of y: Therefore: x = 9 and y = 28

-4 plus 10 equals 6.

This can be solved a number of ways. In thi case I prefer substitution. y-3=7 simplifies to y=10. Substitute 10 in for y so you get x+3(10)=6. Simplify this and you get x=-24

If x equals 10 and y equals 10, then 9x plus 8y equals 170.

-10

x=10

12 + 10 + 11 equals 33

-10 plus 10 equals 0.

61

what is the solution of x-5y=10 and 2x-10y=20